Temporal cycles and their relationship with the sky among the Toba of Western Formosa, Argentina - Gómez, Cecilia Paula (2024)
Fil: Natalini Diaz, María Antonella. Pontificia Universidad Católica Argentina. Facultad de Humanidades y Ciencias Económicas; Argentina